And a Good Time Was Had by All! - Norman L Jones (Canadian Respiratory Journal)
As I write this, the American Thoracic Society 2000 meeting held in Toronto has been over for a week. From every point of view it seems to have been a great success. While having the drawbacks of very large meetings, with some tiresome separation between different sessions, one could not complain about the depth of coverage, with over 6000 poster and slide presentations. I was particularly impressed with the number of senior researchers who took part and demonstrated amply that they were not merely names from the past but had much to offer research fellows, especially on a one-to-one basis. One could find standing in front of a poster -- Sol Permutt, Bob Hyatt, John West, Ann Woolcock, Neil Pride and many others who gave freely of their time, experience and wisdom. There can be no better meeting showcasing international respiratory research from all over the globe. The Canadian Thoracic Society (CTS) was prominent in the organization and presentation, and deserves to feel proud of the meeting's success; the Society's annual dinner was well and enthusiastically attended. At the dinner, Dr Clarence Guenter gave the Christie Lecture, which will appear in the Journal before the end of the year.